Gerry Adams an unauthorised life - O'Doherty, Malachi 1951- (Faber & Faber Limited, 2017)
"How did Gerry Adams grow from a revolutionary street activist - in perpetual danger of arrest and assassination - into the leader of Sinn Féin, with intimate access to the British and Irish Prime Ministers and the US President? And how has he outlasted them all? Drawing on newly available intelligence and scores of exclusive interviews, Malachi O'Doherty's meticulously researched biography sheds light on the history of this extraordinary shape-shifter."--